Structural and functional characterization of elastases from horse neutrophils. - Dubin, A (1994)
In order better to understand the pathophysiology of the equine form of emphysema, two elastinolytic enzymes from horse neutrophils, referred to as proteinases 2A and 2B, have been extensively characterized and compared with the human neutrophil proteinases, proteinase-3 and elastase. Specificity studies using both the oxidized insulin B-chain and synthetic peptides revealed that cleavage of peptide bonds with P1 alanine or valine residues was preferred. Further characterization of the two horse elastases by N-terminal sequence and reactive-site analyses indicated that proteinases 2A and 2B have considerable sequence similarity to each other, to proteinase-3 from human neutrophils (proteinase 2A), to human neutrophil elastase (proteinase 2B) and to a lesser extent to pig pancreatic elastase. Horse and human elastases differed somewhat in their interaction with some natural protein proteinase inhibitors. For example, in contrast with its action on human neutrophil elastase, aprotinin did not inhibit either of the horse proteinases. However, the Val15, alpha-aminobutyric acid-15 (Abu15), alpha-aminovaleric acid-15 (Nva15) and Ala15 reactive-site variants of aprotinin were good inhibitors of proteinase 2B (Ki < 10(-9) M) but only weak inhibitors of proteinase 2A (Ki > 10(-7) M). In summary, despite these differences, the horse neutrophil elastases were found to resemble closely their human counterparts, thus implicating them in the pathological degradation of connective tissue in chronic lung diseases in the equine species.